Electrolyte Optimization Study on Dry Cell Generator Electrolysis System for Producing Hydrogen Gas Using RSM Method (Response Surface Method) - Salsabila Tri Rahmi; Efran Ustia Rahmad; Devi Purnamasari; Rahadian Zainul (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
This study aims to determine the optimum condition of hydrogen gas produced through the electrolysis process of dry cell generators using RSM progran. To produce hydrogen gas is done through the method of water electrolysis by decomposing the molecule H2O into hydrogen gas and oxygen gas with the help of direct electric current. Hydrogen gas productivity by electrolysis method applied to DC generators using 4/4 plate electodes (Cu/Al) as cathodes and NaNO3 solutions as electrolytes. The current and voltage used in this electrolysis process is 0.6 ampere and 2 volts for 1 hour. The concentration of hydrogen gas produced is determined using the MQ-8 sensor. The optimum condition of hydrogen gas concentration obtained is at NaNO 31 M concentration and 60 minutes with hydrogen concentration produced as much as 143.393 ppm. The verification result value for hydrogen gas concentration is 144 ppm, so the program's recommended solution is good enough.